Spatio-temporal patterns of air pollution in China from 2015 to 2018 and implications for health risks - Kuerban, Mireadili; Waili, Yizaitiguli; Fan, Fan; Liu, Ye; Qin, Wei; Dore, Anthony J.; Peng, Jingjing; Xu, Wen; Zhang, Fusuo (Environmental pollution (1987), 2020)
China has been seriously affected by particulate matter (PM) and gaseous pollutants in the atmosphere. In this study, we systematically analyse the spatio-temporal patterns of PM2.5, PM10, SO2, CO, NO2, and O3 and the associated health risks, using data collected from 1498 national air quality monitoring sites. An analysis of the averaged data from all the sites indicated that, from 2015 to 2018, annual mean concentrations of PM2.5, PM10, SO2 and CO declined by 3.2 μg m−3, 3.7 μg m−3, 3.9 μg m−3, and 0.1 mg m−3, respectively. In contrast, those of NO2 and O3 increased at rates of 0.4 and 3.1 μg m−3, respectively. Except for O3, the annual mean concentrations of all pollutants were generally the highest in North China and lowest in the Tibetan Plateau. The concentrations were generally higher in the north of the country than in the south. In all regions of China, the pollutant concentrations were the highest in winter and lowest in summer, except for O3, which showed an opposite seasonal pattern. Overall, the seasonal mean concentrations of all the pollutants (except for O3) significantly decreased between the same seasons in 2018 and 2015, whereas the seasonal mean O3 concentrations generally significantly increased, and/or remained at stable levels in all four seasons except for winter. Diurnal variations of all pollutants (except for O3) exhibited a bimodal pattern with peaks between 8:00 and 11:00 a.m. and 9:00 and 12:00 p.m., whereas O3 exhibited a unimodal pattern with maximum values between 5:00 and 7:00 p.m. No significant differences in the daily mean concentrations of all pollutants were found between weekdays and weekends in all regions, except for PM2.5 and PM10 in Northeast China. In Northwest China and Southeast China, PM2.5 showed stronger correlations with NO2 relative to SO2, suggesting that NOx emission control may be more effective than SO2 emission control for alleviating PM2.5 formation. Compared with 2015, the total PM2.5-attributable mortality, number of respiratory and cardiovascular diseases, and incidence of chronic bronchitis decreased overall by 23.4%–26.9% in 2018. In contrast, for O3-attributable deaths, there was an increase of 18.9%. Our study not only improves the understanding of the spatial and temporal patterns of air pollutants in China, but also highlights that synchronous control of PM2.5 and O3 pollution should be implemented to achieve dual benefits in protecting human health. [Display omitted] •Hourly concentrations of six air pollutants were analysed at1498 sites in China.•Except O3 and NO2, all the pollutants concentrations decreased annually.•O3 peaked in the Tibetan Plateau, whereas the other pollutants in North China.•The diurnal variations of all pollutants displayed a bimodal pattern except for O3.•O3 pollution should be reduced to maximise the protection of human health. Our study highlights the large variability in the spatial and temporal patterns of air pollutants over China and indicates that O3 pollution should be given greater consideration.